Diagnosis and treatment of diaphragmatic endometriosis: results of an international patient survey. (May 2021) - Piccus, Rachel; Mann, Christopher; Sutcliffe, Robert P.
Abstract: Objectives: To quantify the delays associated with the diagnosis and treatment of diaphragmatic endometriosis (DE), and to evaluate patient-reported postoperative outcomes. Study design: An anonymous survey was designed to collect data regarding demographics, duration and nature of DE symptoms, type of surgery and postoperative outcomes. Members of endometriosis patient associations in 14 countries were invited to complete the survey if they had been diagnosed with DE. Factors associated with postoperative outcomes were analyzed using Mann-Whitney U and Fisher's exact tests. Results: Data was available from 136 respondents (median age 34 years). 98 % of respondents were from Europe, North America or Oceania. The most frequently reported symptoms of DE were moderate-severe pain in the upper abdomen (68 %), chest (64 %) and shoulder (54 %). Pain was right-sided in 54 %, left-sided in 11 % and bilateral in 35 %. Of 122 respondents who initially consulted a primary care physician, a gynaecology referral occurred after a median of five consultations (range 1–100). The median time between first primary care consultation and diagnosis of DE was two years (range 0–23). 31 % were diagnosed >1 year after their first gynaecology consultation (range 1–13 years), and 30 % required two or more laparoscopies before diagnosis. 116 respondents underwent surgical treatment. Postoperative data was available for 113 respondents, and 65 % reported either a significant improvement or complete resolution of symptoms. There was no significant difference in age (P = 0.19), timing of diagnosis (P = 0.59) or type of procedure (excision or ablation) (P = 0.13) between respondents who did and did not experience symptomatic relief after surgery. 61 % reported long-lasting symptomatic relief after a median of 1 year, whilst 39 % reported ongoing moderate-severe pain or have undergone further surgery for recurrent symptoms. Conclusion: The diagnosis and treatment of diaphragmatic endometriosis is often delayed, due to lack of awareness by patients and healthcare professionals. The diagnosis of DE requires a high index of suspicion and involvement of surgeons trained in laparoscopic liver mobilization. Recurrent symptoms are common following surgical treatment, and international collaborative studies are required to determine the long-term outcomes of this condition.